2012
DOI: 10.5172/conu.2012.40.2.210
|View full text |Cite
|
Sign up to set email alerts
|

An experimental study on the effectiveness of a mutual support group for family caregivers of a relative with dementia in mainland China

Abstract: When caring for an older relative with dementia, family members experience considerable distress and burden. Literature reviews show that supportive group interventions for these caregivers have significant positive effects on improving their distress and quality of life, but not consistent and conclusive. Limited research is found in Asian populations. This study tested the effectiveness of a 12-session bi-weekly mutual support group program for Chinese family caregivers of a relative with dementia in Guangzh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
0
5

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 30 publications
2
27
0
5
Order By: Relevance
“…This result draws attention to the crucial issue of what has been called "family burden" the painful, often debilitating and health endangering experience of caring for seriously mentally ill family members’ day in and day out. These experiences may be especially strong in Asian countries such as China in which the family, rather than the state or society, has a heavy burden of responsibility for mentally ill relatives, extending even to fiscal responsibility for their occasional damage of neighborhood property or criminal conduct [23,24]. …”
Section: Discussionmentioning
confidence: 99%
“…This result draws attention to the crucial issue of what has been called "family burden" the painful, often debilitating and health endangering experience of caring for seriously mentally ill family members’ day in and day out. These experiences may be especially strong in Asian countries such as China in which the family, rather than the state or society, has a heavy burden of responsibility for mentally ill relatives, extending even to fiscal responsibility for their occasional damage of neighborhood property or criminal conduct [23,24]. …”
Section: Discussionmentioning
confidence: 99%
“…Some of the papers reporting face‐to‐face studies are linked, but for the purposes of the review when reporting the outcomes for the interventions each paper will be individually included as they each present different outcome data from the original study. Linked research papers are: Andren and Elmståhl (, ); Gaugler, Reese, and Mittelman (); Gaugler, Roth, Haley, and Mittelman (), Gaugler, Roth, Haley, and Mittelman () and Mittelman, Roth, Clay, and Haley (); Laakkonen et al () and Laakkonen et al (); and Wai Tong and Lee (), Wang and Chien () with Wang, Chien, and Lee (). Therefore, the scoping review identified 28 original studies represented by 36 research papers.…”
Section: Methodsmentioning
confidence: 99%
“…, Wang et al . ). In fact, in China, caring for older people is assigned to family members by law (The 11th Standing Committee of the National People's Congress ).…”
Section: Introductionmentioning
confidence: 97%
“…, Wang et al . ). In China, nurses are in an ideal position to lead homecare for people with dementia and support caregivers because they make up the majority of health professionals in Community Care Centres and have more contact and closer relationships with the local residents compared with other health professionals (Wei et al .…”
Section: Introductionmentioning
confidence: 97%